Analyse Profitability, Asset Growth, Deviden Payement, Interest Rate and Inflation Rate to Capital Structure of Consumer Goods Companies listed in Indonesian Exchange for period 2009-2011 - Lasni Herti Suryani; Zulbahridar '; Yesi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is done to give empiric proof about the effects of profitability, asset growth, deviden payment, interest rate and inflation rate to capital structure of consumer goods companies listed in Indonesian Stock Exchange for period 2009-2011. The population of this research are 33 consumer goods companies that is used as samples in this research. The analytical method used in this research is multiple linear regression with the help of SPSS program ver. 17,0. From the test result, regression simultan test (test F) shows that all independent variables (profitability, asset growth, deviden payment, interest rate and inflation rate) have significant effect to capital structure variable , partial regression tests (test T) shows that asset growth variable and deviden payment have significant effect on capital structure variable. The effect caused by this four independent variables all together with the dependent variables is 31,60%, while the rest of 68,40% is affected by other variables that is not include in this research. The result of this research shows that only asset growth and deviden payment have the significant effect to capital structure, while the other variables (profitability, interest rate and inflation rate) have insignificant effect to capital structure. Keywords: Capital Structure, Profitability, Asset Growth, Deviden Payment, Interest Rate, and Inflation Rate